The Direction, Timing and Causality Relationships Between The Cyclical Components of Real and Financial Variables During The Financial Liberalization Period in Turkey - Aysu Insel; Mehmet Ali Soytaş; Seda Gündüz (Turkish Economic Association, 2004)
The purpose of this paper is the determination of sources and pattern of business cycle in Turkey throughout the period 1988-2002 using quarterly data. The question of the paper is Has financial liberalization increased the fragility of the financial and real sides of the Turkish economy? The quantitative analysis of the paper includes the cross correlation and causality analysis. Financial development indicators are the bank credits and capital flows, efficiency indicators are the domestic and foreign interest rate spreads. It has been found that the pattern of real GDP is determined by demand side variables, whereas the source of fluctuations in the real GDP is the financial variables in Turkey. External spread, capital flows, and domestic spread are the transmission channels of a shock to the real economy.
Keywords: C32; E32; E44; 330; business cycle; liberalization; decomposition; efficiency indicator; development indicator; Turkey